Fungal Pneumonia in The Immunocompetent Host: A Possible Statistical Connection Between Allergic Fungal Sinusitis with Polyposis and Recurrent Pulmonary Infection Detected by Gastroesophageal Reflux Disease Scintigraphy - Burton, Leticia (Mol Imaging Radionucl Ther, 2020)
OBJECTIVES: Fungal pneumonia in the immune competent host is a rarity with few reported cases in the literature. We present a series of 7 cases of recurrent fungal pneumonia in association with allergic fungal rhinosinusitis and gastroesophageal reflux disease (GERD). We hypothesised that recurrent infection may have been transported from the infected paranasal sinuses into the lung by GERD as the process was terminated by surgical fundoplication in 2 of these patients. METHODS: Patients were recruited into the study if they were immune competent and had recurrent fungal pneumonia and GERD. Allergic fungal rhinosinusitis was proven by biopsy. GERD was investigated by a scintigraphic test that assessed local oesophageal disease, lung aspiration and head and neck involvement with a hybrid gamma camera and X-ray computed tomography. RESULTS: All patients were shown to have GERD with 5/7 showing paranasal sinus contamination and 7/7 showing laryngopharyngeal involvement and 6/7 lung aspiration. One patient had characteristics strongly predictive of aspiration. Fundoplication led to cessation of fungal lung infection in two patients. CONCLUSION: Recurrent fungal pneumonia in the immune competent host should raise the possibility of re-infection from the paranasal sinuses, especially in patients with GERD.